2014
DOI: 10.1002/app.40892
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and properties of a polyhedral oligomeric octadiphenylsulfonylsilsesquioxane

Abstract: A novel polyhedral oligomeric octadiphenylsulfonylsilsesquioxane (ODPSS) was synthesized from octaphenylsilsesquioxane and benzenesulfonyl chloride via a Friedel-Crafts reaction with a high yield. ODPSS was identified by Fourier transform infrared spectroscopy, 1 H-NMR, 13 C-NMR, 29 Si-NMR, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), wide-angle X-ray diffraction, and elemental analysis to be a kind of polyhedral oligomeric silsesquioxane of a T 8 R 8 structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Indeed, as expected AlCl 3 catalyzed Friedel-Crafts acylation and sulfonation provide phenyl cages where meta selectivity is 480% as the SiO 1.5 corner offers electron withdrawing properties akin to -CF 3 . [15][16][17][18] In contrast to traditional aromatic bromination, we have reported that uncatalyzed bromination of [PhSiO 1.5 ] 8 in refluxing dichloromethane leads, after recrystallization to [o-BrPhSiO 1.5 ] 8 , where ortho bromination dominates, 85%. 16 This result is supported by both single crystal X-ray diffractometry and selective Si-C bond cleavage with F À /H 2 O 2 .…”
mentioning
confidence: 99%
“…Indeed, as expected AlCl 3 catalyzed Friedel-Crafts acylation and sulfonation provide phenyl cages where meta selectivity is 480% as the SiO 1.5 corner offers electron withdrawing properties akin to -CF 3 . [15][16][17][18] In contrast to traditional aromatic bromination, we have reported that uncatalyzed bromination of [PhSiO 1.5 ] 8 in refluxing dichloromethane leads, after recrystallization to [o-BrPhSiO 1.5 ] 8 , where ortho bromination dominates, 85%. 16 This result is supported by both single crystal X-ray diffractometry and selective Si-C bond cleavage with F À /H 2 O 2 .…”
mentioning
confidence: 99%
“…In our previous work, diphenylsulfone-containing POSS (ODPSS) was synthesized successfully and introduced into an epoxy resin [32]. It is a functionalized (PhSiO 3/2 ) 8 with high thermal stability, while the solubility of ODPSS in commonly used solvents is not desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Octaphenylsilsesquioxane (OPS) is an important member of the polyhedral oligomeric phenylsilsesquioxane (POSS) family, which has attracted much attention due to its excellent thermal stability properties. However, the chemical inertness and low solubility in most organic solvents of OPS restrict its broader application. , Over the last two decades, OPS modified by a variety of groups has been reported, such as nitrated octa­(phenyl)­silsesquioxane (NO 2 -OPS), , aminated octa­(phenyl)­silsesquioxane (NH 2 -OPS), , octadiphenylsulfonylsilsesquioxane (ODPSS), octamethyldiphenylsulfonylsilsesquioxane (OMDPSS), , and polycarboxyl octaphenylsilsesquioxanes . ODPSS and OMDPSS improved the solubility of OPS by 400 and 3000 times in dichloromethane, respectively.…”
Section: Introductionmentioning
confidence: 99%